Contribution of group dynamics factors to technology adoption among Malaysia cocoa farmer clusters - Kasin, Philph@Ramli (2012)
The contribution of Group Dynamics Factors (GDF) is crucial in group development. However, the extent of their influence on cocoa farmer’s group performance in Malaysia is never deliberated. This research attempts to look at the contribution of GDF to the successful technology adoption (TA) of Malaysian Cocoa Farmers Clusters (CFC). The main objective is to determine GDF that influence the success of TA among CFC under the program of Malaysia Cocoa Board (MCB) in Malaysia. It also attempts to identify the discriminating factors between successful and less successful TA among CFCs. The approach used in this study involves a systematic collection of data and information on 136 samples of CFC in Malaysia which involved 681 members of CFC. Stratified sampling method was employed in this study. The data investigated were GDF that consists of collection of individual units that combine together to form an integrated and a complex whole. The GDF were divided into three main components which were individual inputs (demographic), group inputs and external inputs (MCB extension agent coordination ability). The interaction among the GDF during group process led to TA. Multiple Regression Analysis (RA) was used to determine the predictors of successful TA among CFC. Discriminant Analysis (DA) was applied to verify GDF that differentiate between successful and less successful CFC in terms of TA. The study shows that the success of TA among CFC is contributed by the GDF. These are membership attraction; EA CFC coverage; cocoa farming experience; and the role of participation in CFC. The greatest predictor was membership attraction. The study also reveals the existence of differences in GDF between less successful and successful CFC. The findings of this study indicate significant role of cluster in spearheading TA among cocoa farmers in a larger scale. It provides a road map for MCB to better understand the breakdown and the nature of cocoa farmers’ clusters so as to create realistic prospect on cocoa farmers’ development through cluster approach.